Effects of Drying Methods on Different Characteristics of Chokeberry - Ceylan, Cigdem Mustu; Cakmakoglu, Selma Kayacan; Bekiroglu, Hatice; Yaman, Mustafa; Akcicek, Alican; Sagdic, Osman; Karasu, Salih (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2024)
This research was aimed to determine effect of four different drying techniques, namely Hot Air Drying (HAD), Vacuum Drying (VD), Ultrasound-Assisted Vacuum Drying (USVD), and Freeze Drying (FD) on drying time, total bioactive content, phenolic and anthocyanin profile, surface characteristic and color change of chokeberries. The novelty of this study is the first application of USVD in chokeberry drying. The drying times were recorded as 2100, 1380, and 1200 minutes for HAD, VD, and USVD, respectively, indicating that the application of ultrasound significantly reduced the drying time. Total Phenolic Content (TPC) value of the dried samples varied between 53.15 and 81.18 GAE/g. The individual phenolic and anthocyanin content were determined by HPLC methods. The phenolic profile of the chokeberries showed that protocatechuic acid, catechin, and chlorogenic acid were the major phenolic compounds. The protocatechuic acid value changed between 707.04 and 1126.49 mg/100 and FD showed highest protocatechuic acid value. The anthocyanin profile test showed that the cyanidin-3-Ogalactoside was the most prevalent anthocyanin and its value was found as 27725-198674 mcg/100g. Delta E value was used to determine effect of drying techniques on color change of the dried samples. Delta E value was found as 8.07-11.98. SEM analysis was used to determine effect of drying on surface characteristic of chokeberries. The samples dried by FD and USVD showed more porous structure. This study concluded that USVD emerged as a promising alternative to VD and HAD due to its shorter drying time, higher retention of bioactive compounds, and better color preservation.
Keywords: Anthocyanin; Bioactive compounds; Chokeberry; Phenolic compound; Ultrasound-assisted vacuum drying; ARONIA-MELANOCARPA; ANTIOXIDANT CAPACITY; ULTRASOUND; QUALITY; VACUUM; POLYPHENOLS; KINETICS; AIR; EXTRACTION; PHENOLICS; Engineering